A promising approach to develop nanostructured lipid carriers from solid lipid nanoparticles: preparation, characterization, cytotoxicity and nucleic acid binding ability - Oner-Bozkurt, Ezgi (My University, 2020)
We aimed to develop nanostructured lipid carriers (NLCs) displaying similar characteristics – particle size, polydispersity index, and zeta potential – with the model solid lipid nanoparticles (SLNs) for better comparability. By considering the hydrophilic-lipophilic balance values of solid and liquid lipids, five out of six NLCs and eight out of eight cationic NLCs (cNLCs) were successfully prepared with similar characteristics to their precursor SLN and cationic SLNs (cSLNs), respectively. Among cationic formulations, two cSLNs containing different surfactant/co-surfactant concentrations (4% and 8% S/CoS; w/w) and their cNLC versions prepared with Labrafac lipophile WL 1349 (LWL) or Labrafac PG were selected to compare cytotoxicity, stability, and nucleic acid binding ability. All formulations are well-tolerated by L-929 cells, cSLNs being least toxic. The formulations containing 4% S/CoS had higher stability after 24-months. All nanoparticles formed complexes with pDNA (Binding ability: cNLCs > cSLNs). cSLN and LWL-cNLC containing 4% S/CoS showed the highest pDNA binding capacity in each group, and their spherical/oval shape was revealed by electron microscopy. However, they did not form complexes with siRNA. The developed approach has the potential to simplify the production of (c)NLCs having similar physicochemical properties with the optimum (c)SLN and may provide better insight for (c)SLN vs. (c)NLC comparison studies.
PUBLISHED
Keywords: Solid lipid nanoparticles; nanostructured lipid carriers; cytotoxicity; nucleic acid delivery; plasmid DNA; siRNA; Labrafac lipophile WL 1349; Labrafac PG; Genes & Society; Nanoscience & Materials; Drug Delivery Systems; Drug development; Nano Biotechnology; Nanotechnology; Health